2004
DOI: 10.1023/b:abme.0000019179.87974.7d
|View full text |Cite
|
Sign up to set email alerts
|

Servo-Controlled Pneumatic Pressure Oscillator for Respiratory Impedance Measurements and High-Frequency Ventilation

Abstract: Abstract-The ability to provide forced oscillatory excitation of the respiratory system can be useful in mechanical impedance measurements as well as high frequency ventilation (HFV). Experimental systems currently used for generating forced oscillations are limited in their ability to provide high amplitude flows or maintain the respiratory system at a constant mean pressure during excitation. This paper presents the design and implementation of a pneumatic pressure oscillator based on a proportional solenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
1
23
1
1
Order By: Relevance
“…Test lung compliance was validated across the full range of PAW used during the study. Using a forced oscillation technique (11), the resonant frequency of the test lung was determined to be between 1.2 and 5.5 Hz for all conditions studied.…”
Section: Methodsmentioning
confidence: 99%
“…Test lung compliance was validated across the full range of PAW used during the study. Using a forced oscillation technique (11), the resonant frequency of the test lung was determined to be between 1.2 and 5.5 Hz for all conditions studied.…”
Section: Methodsmentioning
confidence: 99%
“…This approach obviated the need to make assumptions about the extent to which gas behavior was isothermal or adiabatic. It has previously been shown that in systems like ours, polytropic rather than purely isothermal or adiabatic conditions may exist at the frequencies we studied (28). We subsequently conducted a more extensive evaluation of the HW because of its favorable performance and relative ease of use.…”
Section: Methodsmentioning
confidence: 99%
“…Once pressure and flow have been recorded, digital signal processing techniques based around the use of the fast Fourier transform are used to calculate impedance simultaneously at all the different frequencies involved (Bates, 2009). There are a variety of different devices that have been used to apply multifrequency (broadband) oscillations in _ V to the lungs, the most common being loudspeakers (Landser et al, 1976) and piston pumps (Kaczka and Lutchen, 2004;Schuessler and Bates, 1995), but in all cases the basic principles of impedance calculation remain the same.…”
Section: Forced Oscillation Techniquementioning
confidence: 99%